Functional analysis of circadian clock gene timeless in temperature compensation mechanism - Singh, Samarjeet (Jihočeská univerzita, 2020)
This thesis is focussed on investigating the role of the circadian clock gene timeless in the temperature compensation mechanism in Drosophila melanogaster. To conduct the studies presented in this thesis advanced gene editing technique, CRISPR/Cas9, was used to target timeless and to create a variety of mutations. Application of various reverse genetics tools and behavioural methods described here contributed to the elucidation of timeless role in temperature compensation of the circadian clock.
Functional analysis of circadian clock gene timeless in temperature compensation mechanism
Keywords: Reverse genetics; CRISPR/Cas9; Drosophila melanogaster; timeless; circadian clock; temperature compensation; screening; Reverse genetics; CRISPR/Cas9; Drosophila melanogaster; timeless; circadian clock; temperature compensation; screening